Assessment of medical personnel knowledge about the function of transplant coordinator with reference to current Polish legislation - Watrakiewicz-Hurko, Olga; Belowska, Jarosława; Sienkiewicz, Zofia; Dykowska, Grażyna; Gotlib, Joanna (Polish Journal of Public Health, 2014)
Introduction. Initially, a transplant coordinator assisted in the process of removal and transplantation of organs. The most important rule in the Polish legislation is the Act of July 17th, 2009, amending the Act on removal, preservation, and transplantation of cells, tissues, and organs. Professional qualifications of a transplant coordinator are specified by the Regulation of the Minister of Health of December 4th, 2009 on detailed conditions of removal, preservation, and transplantation of cells, tissues, and organs.Aim. The study aimed to assess the knowledge of medical personnel about the function of a transplant coordinator with reference to the current Polish legislation.Material and methods. The study was conducted in April 2013 among 100 selected health professionals (25 physicians, 62 nurses, and 13 persons representing other medical professions) with the use of a questionnaire comprising 42 close-ended simple choice questions and one multiple-choice question. They were referring to various aspects associated with the legal axiology of transplantation, procedure of organ donation, and tasks of a donation coordinator, as well as one open-ended question about the age of respondents.Results. Statistically significant differences between the occupational groups were found in relation to questions about legal and medical aspects. As many as 21 nurses (34%), 26 physicians (92%), and 6 persons representing other medical professions (46%) (p